Skin Histopathology of Diabetes Mellitus Rats Treated with Edible Nest Swiftlets (Aerodhramus fuciphagus) Ointment - Dita Ayulia Dwi Sandi; Yaumi Musfirah (Majalah Obat Tradisional, 2023)
The edible nest swiftlets are suspected to contain sialic acid that can increase the process of cell growth that can reduce the formation of scar tissue and accelerate wound healing. This study aimed to determine the effect and the optimal dosage of edible nest swiftlets ointment on skin histopathology of diabetes mellitus rats that suffered a scratch wound. This study used 25 male white rats, divided into 5 groups, all groups were treated with betadine and the intervention of group 1 was vaseline only (control group), group 2, 3, and 4 were edible nest swiftlets (ENS) ointment with 10%, 20%, and 30% concentration and group 5 were the sanoskin as control positive. The rats were injured in the back area and given the treatment according to the group once a day for 14 days. Skin tissue was taken to make histopathologic preparations for observation on the 0th, 7th, and 14th days. The parameters observed included the number of macrophages, neo-capillarization, and fibroblasts. The result on the 14th day showed that the number of macrophages in the control group, sanoskin group, and ENS 10%, 20%, and 30% group was 3.8±5.019; 3.2±2.489; 1.84±2.387; 1.8±2.049 and 1.2±1.095. The result of neocapillilization were 1.28±1.673; 1.4±1.673; 2.8±1.778; 5.4±4.159; and 15±30.773. The conclusion showed there was a significant difference and there was the effect of edible nest swiftlets ointment on the number of macrophages, the number of neocapillilization, and the density of fibroblasts on the rats with diabetes mellitus that suffered a scratch wound.